Molecular evaluation of mutations in acute myeloid leukemia patients from Turkey: A single-center study. Issue 41 (15th October 2021) - Merdin, Alparslan; Dal, Mehmet Sinan; Kizil Çakar, Merih; Bahsi, Taha; Düzkale, Neslihan; Yildiz, Jale; Bakirtaş, Mehmet; Başçi, Semih; Darçin, Tahir; Şahin, Derya; Tetik, Ayşegül; Uncu Ulu, Bahar; et al.
Abstract : Abstract: Certain genetic mutations could have a role in the etiology of acute myeloid leukemia (AML). Hereby, in this study, we primarily aimed to investigate the distribution of genetic mutations in AML patients. We also attempted to analyze the incidence of genetic mutations in AML patients from Turkey. This retrospective study included a total of 126 patients diagnosed with AML, who had molecular mutation test results or records in their patient files. The patients who were not citizens of the Republic of Turkey were not included in the study. It was observed that analyses for at least 1 c-kit exon mutation had been carried out on 76 patients, which detected no c-kit mutation among the types of genetic mutations investigated in all of those 76 patients. We found the frequency of FMS-like tyrosine kinase 3-internal tandem duplication mutation as 25%. The prevalence of translocation(15;17) was approximately 11% and the prevalence of translocation(8;21) was % 6.25. In addition, we also showed that the frequency of inversion16 was nearly 3.7%. Lastly, the possibility of c-kit mutation in AML patients from Turkey might actually be low.